Proceso de adopción de las Normas Internacionales de Información Financiera NIIF en las entidades sin animo de lucro en Armenia (Colegios de carácter privado) año 2014 (2015)
The globalization is not a process in beginning, it is the social, cultural and economic reality in which we are immersed, of this one, the countable factor becomes detached for the economic root unleashing a set of structural changes of which Colombia seems even to be passing very small. In reference to this it is of thinking that there is still known very little of the effect that is going to have the application of the International Norms of Financial Information NIIF or the IFRS (International Financial Reporting Standars) in the country, since apparently the information is homogenized by cases already seen in other countries, but perhaps: will the economic situation of the entities be born in mind without lucre fortitude?, although to refer to this one would include a wide bogey, we will center the study on the educational sector deprived of the city of Armenia, which due to the wide one and enough alertness will contribute precise information on the convergence that will have to initiate in this 2015.